Reformasi Dalam QS. Al-Kahfi: Telaah Konsep Al-IshlÄh Wa At-TaghyÄ«r SholÄh ShulthÄn Serta Relevansinya Terhadap Fenomena Radikalisme di Indonesia - Islamy, Mohammad Rindu Fajar; Baharuddin, Didin (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Reform in QS. Al-Kahf: Examining the Concept of Al-IshlÄh Wa At-TaghyÄ«r SholÄh ShulthÄn and Its Relevance to the Phenomenon of Radicalism in Indonesia This study aims to analyze the concept of Al-Ishlah wa At-Taghyir which was initiated by Sholah As-Shultan an international scholar and how its relevance to the phenomenon of radicalism in Indonesia. Studies of radicalism, terrorism and extremism have attracted the interest of scientists after the rampant acts of terror that occurred in Indonesia in the last two decades, such as the 2002 Bali bombings, and others. Reforms and improvements to deviations are fundamental things in human life, even the discourse is very much considered by Al-Quran Al-Karim. In QS Al-Kahf, there are several manhajs that are full of reform models to achieve community civilization to become more religious. The research was conducted through a qualitative approach. Through a literature study of Sholah Sulthan’s primary work entitled SÅ«rah Al-Kahfi ManhajiyyÄt FÄ« Al-IslÄh Wa At-TagyÄ«r DirÄsÄt Ta’shÄ«liyyah TathbÄ«qiyyah, the secondary works were taken from other works. The results of the study show several conclusions including: 1) Reform and change are very much considered in the Qur’an, 2) in the QS. Al-Kahf forms of reform reform methods include several forms such as Manhajiyyatu At-Tadarruj min Al-Istid’Äf ilÄ Al-HiwÄr wa MinhÄ ilÄ At-TamkÄ«n, Manhajiyyatu Ba’tsu al-Amal Mahma KÄna al-Alam, and 3) Concepts of Al -Ishlah wa At-Taghyir has relevance to the phenomenon of radicalism in Indonesia, among its efforts is to trace the causal factors, then design preventive measures, collaborative efforts from various parties, and be patient with the process